2008
DOI: 10.1007/s10812-008-9023-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exposure of sturgeon roe to low-intensity laser radiation on the hardiness of juvenile sturgeon

Abstract: We present data on the effect of polarized laser radiation in the near IR region of the spectrum with wavelength 808 nm on the resistance of juvenile sturgeon to oxygen deficiency in the habitat when the fertilized roe are briefly exposed to radiation in the organogenesis stage. The magnitude of the stimulating effect depends on the exposure time (t) and power density (P) of the radiation and also on its modulation frequency (F). For optimal irradiation parameters (cw mode, P = 2.9 mW/cm 2 , t = 60 sec), the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…Based on the presented data and also on data obtained previously 2,3,4 we conclude that among the resonant and nonresonant photophysical processes (orientational effect of light, effect of gradient forces, dipoledipole interactions, thermooptic processes) capable of inducing photo biological effects dependent on such laser-specific characteristics as polarization and coherence, the determining influence in the processes studied in this work comes from the orientational effect of light and dipole-dipole interactions. And the orientational effect can appear for anisotropic media with liquid-crystal type ordering (especially domains in membranes and multiple-enzyme complexes) both under conditions when there is no resonant absorption and for weakly absorbing structures, and can initiate a change in their conformations and accordingly their functional characteristics.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Based on the presented data and also on data obtained previously 2,3,4 we conclude that among the resonant and nonresonant photophysical processes (orientational effect of light, effect of gradient forces, dipoledipole interactions, thermooptic processes) capable of inducing photo biological effects dependent on such laser-specific characteristics as polarization and coherence, the determining influence in the processes studied in this work comes from the orientational effect of light and dipole-dipole interactions. And the orientational effect can appear for anisotropic media with liquid-crystal type ordering (especially domains in membranes and multiple-enzyme complexes) both under conditions when there is no resonant absorption and for weakly absorbing structures, and can initiate a change in their conformations and accordingly their functional characteristics.…”
Section: Discussionsupporting
confidence: 78%
“…As our long-term studies have shown, laser radiation, as well as the radiation of super-bright LEDs, has a stimulating effect on fish and their sexual products (caviar and sperm), as well as on the development of gullet crustaceans. 2,3,4 Our previous studies were based on the effect of optical radiation on bioobjects within a single exposure. The question of the most favorable periods of repeated exposure to optical radiation, in which the maximum effect on aquaculture objects is manifested, remains open.…”
Section: Introductionmentioning
confidence: 99%
“…So, by the example of three cyanobacterial strains, it was shown that the response of organisms to pollution of freshwater aquatic ecosystems with zinc is highly dependent on the light level (50). It is known that very low-intensity laser radiation can significantly affect the development of living systems (1,5,(51)(52)(53)(54). In (29), a low-intensity laser preradiation protector effect was found: The pre-exposure of a small region of the mice skin surface to low-intensity helium-neon laser light markedly decreased the toxic effect of lipopolysaccharide.…”
Section: Chronic Experiments With Toxicant and Laser Preirradiationmentioning
confidence: 99%
“…Photobiomodulation (PBM), also known as low-level laser therapy (LLLT), which involves exposing biological objects to monochromatic (laser) or nonmonochromatic (LED) visible or near-infrared light, has been actively developed over the past few decades. Numerous studies have been conducted in order to reveal the mechanism of action, to develop treatment methods and to find out safe treatment modes at the level of both cells (1-3) and various organisms (4)(5)(6). It has been demonstrated that PBM, depending on the physical impact parameters and the condition of the biological object, has a positive or negative, stimulating, overwhelming or regulatory effect on both prokaryotic and eukaryotic organisms (3,(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation